The bioenergetics of COVID-19 immunopathology and the therapeutic potential of biophysical radiances - Surazakov, Arzhan (J Photochem Photobiol B, 2020)
In developing an effective clinical tool against COVID-19, we need to consider why SARS-CoV-2 infections develop along remarkably different trajectories: from completely asymptomatic to a severe course of disease. In this paper we hypothesize that the progressive exhaustion and loss of lymphocytes associated with severe stages of COVID-19 result from an intracellular energy deficit in an organism which has already been depleted by preexisting chronic diseases, acute psychological stress and the aging process. A bioenergetics view of COVID-19 immunopathology opens a new biophysical opportunity to enhance impaired immune function via proposed pathways of photomagnetic catalysis of ATP synthesis, regenerative photobiomodulation and the ultrasonic acceleration of cell restructuring. Moreover, we suggest that a coherent application of multiple biophysical radiances (coMra) may synergistically enhance energy-matter-information kinetics of basal self-regeneration of cells and thus improve immune function and accelerate recovery.